Postoperative hypoparathyroidism after thyroid operation and exploration of permanent hypoparathyroidism evaluation - Wang, Xi; Wang, Shun-lan; Cao, Yang; Li, Chun-qiao; He, Weiping; Guo, Zhu-ming (Frontiers in Endocrinology, 2023)
Background To investigate the risk factors for hypoparathyroidism, discuss the prevention of postoperative hypoparathyroidism, and explore permanent postoperative hypoparathyroidism evaluation (PPHE). Methods A total of 2,903 patients with thyroid nodules were treated between October 2012 and August 2015. Serum calcium and intact parathyroid hormone (iPTH) levels were measured at 1 day, 1 month, and 6 months postoperatively. The incidence and management of hypoparathyroidism were analyzed. The PPHE was established based on the risk factors and clinical practice. Results A total of 637 (21.94%) patients developed hypoparathyroidism, and 92.15% of them had malignant nodules. The incidence rates of transient and permanent hypoparathyroidism were 11.47% and 10.47%, respectively. The iPTH level was lower in patients with malignant nodules who underwent total thyroidectomy (TT) and central-compartment neck dissection (CND). These factors were independently associated with the recovery rate of parathyroid function. The formula for PPHE is as follows: {iPTH} + {sCa} + {surgical procedure} + {reoperation} + {pathologic type}. A scoring system was developed, and we scored low, middle, and high risk of permanent postoperative hypoparathyroidism as 4–6, 7–9, and 10–13, respectively. The differences in the recovery rates of parathyroid function in several risk groups were statistically significant (p < 0.001). Conclusion Simultaneous TT and CND is a risk factor for hypoparathyroidism. The reoperation is not associated with hypoparathyroidism. Identification of parathyroid glands in situ and preservation of their vascular pedicles are key factors in managing hypoparathyroidism. PPHE can forecast the risk of permanent postoperative hypoparathyroidism well.